Connector - HE FUQIAN (2016)
The utility model relates to a USB data transmission equipment's technical field discloses a connector, including gluing core and terminal, the rear end of gluing the core is equipped with a plurality of terminal guiding hole, and the horizontal parallel configuration of a plurality of terminal guiding hole is equipped with the shell fragment pothook on the terminal on gluing the core, glue be equipped with a plurality of parallel configuration on the core and when the terminal gets into gluey core the shell fragment pothook pass the ka tai of terminal guiding hole card including establishing, katai lies in the terminal guiding hole, the outer end of terminal is equipped with the riveting formula structure that is used for fixed wire rod wire and the insulating skin of wire rod, sets up the terminal guiding hole on gluing the core, plays the effect of direction to the installation of terminal to, be equipped with the shell fragment pothook on the terminal, glue and to set up ka tai on the core, the terminal w